An investigation of the role of phosphorylation at Ser211 of the glucocorticoid receptor in ligand-specific transcriptional regulation - Stubsrud, Elisabeth (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2005.